Lubrication analysis for the piston ring of a two-stroke marine diesel engine taking account of the oil supply. (March 2021) - Li, Tongyang; Ma, Xuan; Lu, Xiqun; Wang, Chuanjuan; Jiao, Bowen; Xu, Hanzhang; Zou, Dequan
The piston ring is one of the most important parts of a two-stroke marine diesel engine. It is lubricated by a special mode in which the lubricating oil is directly injected into the liner's inner surface. In this article, taking account of the oil supply, a piston ring lubrication model is developed based on oil mass conservation. The lubrication region of this piston ring–cylinder liner is divided into inlet, core lubrication, and outlet regions, with the oil supply being converted into an oil film. The impact of the width of the core lubrication region on squeezing of the oil is considered. To verify the model, friction force measurements are performed in a reciprocating bench test under fully flooded conditions, and the model is further validated by comparing the minimum oil film thickness with data from the literature. The model is applied to the top ring of a two-stroke marine diesel engine, and the impacts of the oil supply and its design parameters are analyzed.